The protective effects of honey propolis on kainic acid mediated excitotoxicity in rat brain - Swamy, Mummedy (Pusat Pengajian Kesihatan, 2016)
To understand the neuro-protective effects of propolis, the activities of nitric oxide synthase (NOS), glutamine synthetase (GS), caspase-3 and nitric oxide (NO), thiobarbituricacid reactive substances (TBARS), total antioxidant status (TAS) and tumor necrosis factor-a (TNF-a) levels along with the expression of neuronal NOS(nNOS), inducible NOS (iNOS), TNF-a, caspcse-3 and GS were studied in cerebral cortex, cerebellum and brain stem in rats injected with kainic acid (KA) and in rats supplemented with propolis prior to excitotoxic injury with KA. Results of these studies clearly demonstrated that the propolis supplementation attenuated the NOS, caspase-3 activities, NO, and TNF-a concentration in KA mediated excitotoxicity. These studies were also demonstrated the restoration of GS activity and decreased oxidative stress by propolis in kainic acid mediated excitotoxicity. The expression studies of NOS isoforms did not show any change either with KA or propolis supplementation. Changes in expression of caspase-3, TNF-a and GS with KA administration were restored to normal with the prior supplementation of propolis. Hence the propolis can be a possible potential candidate (protective agent) against excitotoxicity and neurodegenerative disorders.